Filling in the Civ-Mil Gap Across the Americas - Teal, Christopher (Hemisferio - Revista del Colegio Interamericano de Defensa, 2020)
This article examines how civilian governments and their militaries across the Americas must confront increased security responsibilities and analyzes consequences to maintain a healthy Civil-Military relationship balance. As elected leaders in the region weigh addressing multiple social challenges, they must pay special attention to how their actions could upend Civil-Military progress and lead to destabilization of democracy if not handled correctly, especially with a rise in populism. Instituting and institutionalizing reforms can have a positive and lasting impact for the region and cement democratic control for years to come.